Technology Adoption in Indian Banking Sectors – 2023 - D. Murugun (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Recent Technology in banking has become even more evident in recent years, as phone, online and mobile banking has revolutionize the way we take care of our finances. In fact, one might argue that the impact of technology in the banking sector has meant that we now have no excuse for being overdrawn or not paying credit card bills on time. In previous generations, the only way to find out how much money you had in the bank was to keep a detailed log book or pay a visit to your local branch and ask the teller to check the ledger for you. Then along came the innovation known as the ATM machine, which allowed us to withdraw cash from hundreds of convenient locations and check our balance while we were at it. Nowadays, with mobile banking apps it’s possible to check your balance any time any place. So before you splash out on a new stereo or home entertainment system you can check your account then and there just to be sure you can afford it. Another one of the Advantages of technology in banking is that it allows us to pay bills quickly and without physical visit. We can arrange to have them paid by direct debit every month at a time that suits us, or we can make one off transfers as and when the bills come in. This means that there’s no longer any need to pay a physical visit to your branch to pay bills and it also means we are more likely to pay them on time. People who find it more difficult to manage their money can arrange for as many bills as possible to be paid just after their salary clears their account so that they know the essentials are covered before they can spend on luxuries. In this paper has been made an attempt on “Technology adoption in Indian Banking Sector.